A Study on the Impact of Digital Finance on Ecological Resilience of the Yangtze River Delta Urban Agglomeration - Luo, Xuchen; Wang, Yan (Journal of Economic, Management and Engineering Research, 2025)
As the core area of China's economic development, the Yangtze River Delta city cluster faces the dual challenges of declining ecological carrying capacity and digital transformation. Digital finance, through technological empowerment and resource reallocation, may become a key driver of ecological resilience enhancement. The purpose of this paper is to explore the impact effect of digital financial empowerment on the Yangtze River Delta (YRD) urban agglomeration, to explore its mechanism of action and to further explore whether there is a chain mediation effect. This study selects the spatial panel data of the YRD urban agglomeration from 2010-2024 as a sample, and analyses them by constructing a two-way fixed-effects model, and at the same time investigates their transmission paths, and puts forward the two mediation effects of technological innovation and energy consumption, and finally, through a Double Difference Model (DID) to further discuss the effectiveness of the pilot policy of ecological compensation, and finally this paper analyses based on the above conclusions, and puts forward the relevant policy recommendations for China's digital entry and healthy development, as well as the enhancement of ecological resilience of China's cities. The empirical results show that: (1) digital finance has a facilitating effect on the ecological resilience of the Yangtze River Delta urban agglomeration. (2) Digital finance mainly plays a role in the state toughness, pressure toughness and response toughness in ecological resilience. (3) Technological innovation and energy consumption play an important role as intermediary variables in the digital financial empowerment of ecological resilience. (4) The pilot policy of ecological environment compensation is effective.